2002
DOI: 10.1007/s00125-001-0769-2
|View full text |Cite
|
Sign up to set email alerts
|

Taq I polymorphism of the vitamin D receptor and risk of severe diabetic retinopathy

Abstract: Neovascularization plays a role in determining the severity of diabetic retinopathy (DR) due to the effects of several angiogenic and growth factors, including vascular endothelial growth factor (VEGF), plateletderived growth factor (PDGF), basic fibroblast growth factor (bFGF) and insulin-like growth factor (IGF-1) [1].Chronic hyperglycaemia induces non-severe diabetic retinopathy (DR) in most patients of long duration, but not severe DR in the majority of them, sug- Abstract Aims/hypothesis. Vitamin D, a mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 29 publications
0
32
1
1
Order By: Relevance
“…Taverna et al in Paris observed 200 patients with type 1 DM and found that the Tt genotype was associated with severe retinopathy. In that study, patients with TT genotype were low risk for severe diabetic retinopathy [26]. We found no association between VDR gene polymorphisms and diabetic retinopathy.…”
Section: Discussioncontrasting
confidence: 51%
“…Taverna et al in Paris observed 200 patients with type 1 DM and found that the Tt genotype was associated with severe retinopathy. In that study, patients with TT genotype were low risk for severe diabetic retinopathy [26]. We found no association between VDR gene polymorphisms and diabetic retinopathy.…”
Section: Discussioncontrasting
confidence: 51%
“…Other gene polymorphisms in the RAGE gene 325 , the TGF-beta1 gene 326 , the VEGF gene [327][328][329][330] , the eNOS (endothelial nitric oxide synthase) gene 330 and vitamin D receptor 331 have also been associated with the presence or severity of DR from case-control studies. A meta-analysis that examined the association between DR in T2DM and polymorphisms in the gene for hyper-homocystinaemia (methylenetetrahydrofolate reductase, MTHFR) found only a marginal association with large heterogeneity between different studies 332 .…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Vitamin D receptor-related genotypes have been associated with diabetic retinopathy in type 1 and type 2 diabetic subjects [249][250][251][252][253][254]. Similar to its known role in bone and calcium metabolism, vitamin D also has roles in insulin resistance and immune function, and it has anti-inflammatory, anti-angiogenic, and anti-fibrotic effects.…”
Section: Nutrition-related Biomarkersmentioning
confidence: 99%